Associative Meaning of Figurative Language Found in Taylor Swift’s Midnights (3am edition) - Sari Murni; Wildi Adila (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
Midnights (3am edition) is a more complex version of Taylor Swift’s album, Midnights. It is also her first autobiographical album because her previous albums were about myths. Midnights album is mostly about her life and discusses people in her past. This research aims at analyzing the content of the songs, how Taylor expresses her story in the past using figurative language, and what Taylor means by using associative meaning in the Midnights (3am edition) album. Data source in this research is spotify and genius website, after that researcher uses a descriptive qualitative method to analyze the data. Data is collected using documentation. Four steps are used to analyze data: domain analysis, taxonomy analysis, componential analysis, and cultural themes. The results of this study show that there are 87 data of figurative language in Midnights (3am edition). The most common figurative language is overstatement, which is as many as 22 (25%), followed by metaphors, as many as 19 (22%) data. Furthermore, there are 83 data associative meanings of figurative language. Connotative meaning is the most common data found in this study, with 64 (77%) data.